The social and clinical determinants of proportions between paternalism and partnership in therapeutic relationships in medicine - Skrzypek, Michał (Polish Journal of Public Health, 2018)
The subject of the article are the contextual determinants of the formula of the therapeutic relationship in medicine with regard to the proportions between paternalism and partnership. The article was inspired by the results of two recent editions of the Organisation for Economic Co-operation and Development (OECD) “Health at a Glance” studies of 2015 and 2017; in their light, Poland ranks at the bottom of ratings concerning patient satisfaction with communication with doctors. According to these studies, the therapeutic relationship in medicine in Polish society appears to be petrified in the paternalist formula, not sufficiently taking into account the autonomy and agency of patients. Based on the analysis of the determinants of a broader tendency, described in Western studies, consisting in the wider development of partnership relationships between doctors and patients, the study will show individual barriers, social ones, including structural and institutional, as well as clinical barriers to implementation in medical practice of the partnership model of therapeutic relationships in medicine, which assumes the active involvement of patients in clinical decision-making as well as in the processes of medical treatment.